2015
DOI: 10.1007/s00726-015-2056-4
|View full text |Cite
|
Sign up to set email alerts
|

Preinduction of heat shock protein 70 protects mice against post-infection irritable bowel syndrome via NF-κB and NOS/NO signaling pathways

Abstract: This study aimed to investigate the protective effects of preinduction of heat shock protein 70 (HSP70) on Trichinella spiralis infection-induced post-infectious irritable bowel syndrome (PI-IBS) in mice. Trichinella spiralis infection significantly reduced HSP70 abundance, ileal villus height and crypt depth, expression of tight junctions, serum lysine and arginine concentrations, and ileal SCL7A6 and SCL7A7 mRNA levels, induced inflammatory response, and activated NF-κB signaling pathway. Meanwhile, the heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Our previous research reported that the intestinal HSP70 level raised during PI-IBS. Furthermore, Preinduction of HSP70 could improve the clinical symptoms of PI-IBS [ 22 , 26 ]. Several studies also demonstrated that HSP70 inhibits the production of proinflammatory cytokines in different cell populations [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research reported that the intestinal HSP70 level raised during PI-IBS. Furthermore, Preinduction of HSP70 could improve the clinical symptoms of PI-IBS [ 22 , 26 ]. Several studies also demonstrated that HSP70 inhibits the production of proinflammatory cytokines in different cell populations [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of HSP70 was induced by heat treatment according to previous report [ 22 ]. The mice were anesthetized with sodium pentobarbital (50 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…In mice, a Trichinella spiralis infection reduced serum arginine (Arg) concentration and the intestinal expression of the SLC7A7 gene (Zhou et al, 2015) that encodes for the basolateral y + L system transporter with an affinity for lysine (Lys), Arg, glutamine (Gln), histidine (His), methionine (Met) and leucine (Leu). This could be related to an increased use of Arg by the enterocytes.…”
Section: Impact Of Inflammation On Amino Acid Intake Digestion Absomentioning
confidence: 99%
“…HSP70 is a member of the heat shock protein family which regulates the stability of intracellular peptides [14]. Its secretion is increased in response to inflammatory reactions [14]; IL-1β is an important pro-inflammatory mediator derived from mononuclear macrophages and lymphocytes.…”
Section: Group Time Point Acth (Pmol/l) Cor (Nmol/l) Ins (Miu/l) C-p mentioning
confidence: 99%
“…Its secretion is increased in response to inflammatory reactions [14]; IL-1β is an important pro-inflammatory mediator derived from mononuclear macrophages and lymphocytes. It mediates the amplification cascade of inflammatory reactions [15,16].…”
Section: Group Time Point Acth (Pmol/l) Cor (Nmol/l) Ins (Miu/l) C-p mentioning
confidence: 99%